Magnetite Functionalized Nigella Sativa Seeds for the Uptake of Chromium(VI) and Lead(II) Ions from Synthetic Wastewater - Patience Mapule Thabede; Ntaote David Shooto; Thokozani Xaba; Eliazer Bobby Naidoo (Adsorption Science & Technology)
The aim of the present study was to utilise pristine and magnetite-sucrose functionalized Nigella Sativa seeds as the adsorbents for the uptake of chromium(VI) and lead(II) ions from synthetic wastewater. Prestine Nigella Sativa seeds were labelled (PNS) and magnetite-sucrose functionalized Nigella Sativa seeds (FNS). The PNS and FNS composites were characterized by Fourier-transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). The FTIR analysis of both adsorbents revealed the presence of vibrations assigned to 1749 and 1739 cm-1 (-C=O) for ketonic group for both adsorbents. The amide (-NH) peak was observed at 1533 and 1527 cm-1 on FNS and PNS composites, respectively, whilst the carboxyl group (-COOH) were observed at 1408 cm-1 on both adsorbents. The XRD results of FNS and PNS composites showed a combination of spinel structure and y-Fe2O3 phase confirming the formation of iron oxide. The influence of operational conditions such as initial concentration, temperature, pH, and contact time was determined in batch adsorption system. The kinetic data of Cr(VI) and Pb(II) ions on both adsorbents was described by pseudo-first-order (PFO) model which suggested physisorption process. The sorption rate of Cr(VI) ions was quicker, it attained equilibrium in 20 min, and the rate of Pb(II) ions was slow in 90 min. Freundlich isotherm described the mechanism of Pb(II) ions adsorption on PNS and FNS composites. Langmuir best fitted the uptake of Cr(VI) ions on PNS and FNS. The results for both adsorbents showed that the removal uptake of Pb(II) ions increased when the initial concentration was increased; however, Cr(VI) uptake decreased when the initial concentration increased. The adsorption of Cr(VI) and Pb(II) ions on both adsorbents increased with temperature.